2014
DOI: 10.1002/chem.201405062
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of N‐Heterocyclic Derivatives of Divalent Germanium, Tin, and Lead

Abstract: A new class of exceptionally stable asymmetric N-heterocyclic germylenes, stannylenes, and plumbylenes has been successfully isolated and characterized by single-crystal X-ray diffraction analysis and multinuclear NMR spectroscopy. Their stability results from tetrameric supramolecular aggregation through strong intermolecular Npy →E(II) (E=Ge, Sn, Pb) interactions involving the nitrogen atom of a neighboring pyridine moiety. The electronic structures and stabilities of the prepared divalent derivatives of Ge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The Ge-N bond lengths of the two compounds are almost identical (av. 1.869 for 3 and 1.856 Å for 4) and basically compatible with those (1.85-1.89 Å) of previously reported germylenes with ligands A-F. 5,8,9,19,28,31,32 However, the N1-Ge1-N2 bond angle of 83.08(12)°in 3 is slightly smaller than that (85.64(9)°) in 4 (Table 1). The C1-C2 distance of 1.360(5) Å in compound 3 belongs to an olefin double bond and is sufficiently shorter than that of 1.473(3) Å in 4.…”
Section: Paper Dalton Transactionssupporting
confidence: 91%
See 1 more Smart Citation
“…The Ge-N bond lengths of the two compounds are almost identical (av. 1.869 for 3 and 1.856 Å for 4) and basically compatible with those (1.85-1.89 Å) of previously reported germylenes with ligands A-F. 5,8,9,19,28,31,32 However, the N1-Ge1-N2 bond angle of 83.08(12)°in 3 is slightly smaller than that (85.64(9)°) in 4 (Table 1). The C1-C2 distance of 1.360(5) Å in compound 3 belongs to an olefin double bond and is sufficiently shorter than that of 1.473(3) Å in 4.…”
Section: Paper Dalton Transactionssupporting
confidence: 91%
“…The germylene molecules found so far demonstrate that delocalized π-systems of central Ge II -rings like B are helpful to improve the molecular stability, compared with those of satu-rated and acyclic products. From this understanding, the fivemembered germylenes with 10π electrons were assembled using the α-diiminate ligands C and F. 8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Ligand D provided 18π electrons to the corresponding aromatic polycyclic germylenes, 30,31 while the 1,2-bis(imino)acenaphthene ligand E formed the 16π-electronic germylenes 32 with less aromatic stabilization. The cationic germylene G-Ge with unusual delocalization in the electronic properties was reported in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…al is [{( t BuNP) 2 ( t BuN) 2 }Mg(thf) 2 ] [5] . Also known are complexes of divalent group 14 elements with bis(amido)diazadiphosphetidinides as ligands [6–8] …”
Section: Introductionmentioning
confidence: 99%
“…34,38 Pyridine-annulated NHSns, which cannot function as chelating ligands to transition metals, 39 have revealed interesting self-assembly into a highly stable tetramer. 40 Guanidinate 41 and amidinate 27,42 ligands have shown unusual behaviour as supporting ligands for Si(II) and Ge(II) (E) as the normal κ 2 -chelating binding mode can change to a bridging mode between E and a transition metal acting as a tether to the E-TM interaction (D). A recent report has demonstrated that low valent Sn can function as either a donor (E) or acceptor (F) to Pd as part of a phosphine-stannylene chelate highlighting the unique behavior of Sn(II) compared to lighter analogues.…”
Section: Introductionmentioning
confidence: 99%